The extraction of resveratrol and other polyphenols from solid winery waste and an investigation into alternative resveratrol recovery techniques - Kriel, Carlie (Stellenbosch : Stellenbosch University., 2020)
Thesis (MEng)--Stellenbosch University, 2020.